Sistem Informasi Penerimaan dan Pengeluaran Kas Pada Klinik Sarfina Sembiring Berbasis Web - Bangun, Joy Erivan Pratama; Perangin-angin, Resianta; Elisabeth, Duma Megaria (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Sarfina Sembiring Clinic is located at Jalan Cinta Karya No. 60 B Sari Rejo Village, Medan Polonia District, which operates in the Community Health Center Sector. The problem that occurs is that the cash receipt and financial expenditure data processing system at the Sarfina Sembiring Clinic is currently still carried out using a manual recording system to provide ineffective and inefficient reports. The researcher aims to research and help solve the problems faced by the Sarfina Sembiring Clinic, namely by designing a web-based cash receipt and disbursement system. With the development of this information system, it is hoped that the clinic will have a better financial system as well as providing effective reports and archive structured reports. The information system created is expected to help the Sarfina Sembiring Midwife Clinic in improving health services and organizational performance, as well as in the administration of cash receipts and disbursements.